Estimation of Passenger Car Equivalent (PCE) Values in Heterogeneous Traffic Using the Time Headway Method on Timor Raya Road, Kupang City - Amy Wadu; Mateus Sodanango; Ludofikus Dumin; Angelita Laapen (Borneo Engineering: Jurnal Teknik Sipil, 2026)
Traffic on urban roads in Indonesia is generally heterogeneous, comprising various vehicle types with distinct characteristics. To analyze heterogeneous traffic flow, all vehicles are converted into Light Vehicle Units (PCU), and this concept forms the basis for the definition of Light Vehicle Equivalent (LPE) in various guidelines. However, the standard PCE values from guidelines such as MKJI 1997 and PKJI 2023 can produce inaccurate traffic performance estimates because PCE values are not universal and are highly dependent on traffic conditions, road geometry, and driving culture in a particular region. This study aims to estimate PCE values using the time-headway method on Jalan Raya Timor in Kupang, Indonesia, which has experienced rapid growth in vehicle volumes, especially motorcycles. The time headway method is considered more dynamic and sensitive in reflecting drivers' perceptions of vehicle spacing, thus providing more accurate PCE values than traditional methods. The results of the study show that the PCE value for motorcycles (MC) ranges from 0.64 to 0.98, while for heavy vehicles (HV) it ranges from 1.05 to 2.16. The vehicle headway time method proved to be more accurate in assessing the volume-capacity ratio (V/C) because it is more sensitive to the time interval between vehicles, resulting in a V/C estimate that is closer to field data compared to the standard PCE method from PKJI.